ANALISIS KECUKUPAN MODAL, EFISIENSI DAN LIKUIDITAS TERHADAP PROFITABILITAS - Susilowati, Yeye; Aini, Nur; Poerwati, Tjahjaning; Rahayuningsih, Reny (Proceeding SENDI_U, 2019)
This study aims to analyze the effect of capital adequacy, efficiency, liquidity on profitability. Using purposive sampling, 135 banking companies listed on the Indonesian stock exchange for the period 2013 – 2017 are determined as a sample. Multiple linear regression was analyzed using SPSS 19 software. The results show that capital adequacy ratio and liquidity have no effect on profitability. Efficiency has a significant positive effect on profitability. Keywords: Profitability (ROA),Capital Adequacy Ratio (CAR), Efficiency (BOPO), Liquidity (LDR).